Unequal exchange is not primarily about monetary value - Alf Hornborg (Nature Communications)
Ecologically Unequal Exchange (EUE) theory reframes trade as asymmetric transfers of biophysical resources from South to North, rejecting monetary value metrics. It challenges both mainstream and Marxian economics by emphasizing material flows over money-based interpretations of global inequality.